Problematic of Languages in the Translation of Animal Science Terms - Aryani, I Gusti Agung Istri; Sudipa, I Nengah; Yadnya, Ida Bagus Putra; Dhanawaty, Ni Made (e-Journal of Linguistics; Vol 13 No 1 (2019): e-jl-January, 2019)
Animal science terms have their specialty in scientific works because the different results of translation from the source language (SL) and target language (TL) can give effect to the meaning. A translator should understand the terms in both languages to be able to consider the problems and finding equivalence of terms for the result of the product. Problematic of languages may occur not only in SL but can be on both sides, SL and TL when the translator is not the native speaker of the language. This study aims at finding problems of language translation for animal science terms and finding the equivalence of terms using English as SL and Indonesian as TL. Qualitative method used in analyzing the data with a description of the meaning of terms in their translation within the direct interview information. Majorly, problems found in TL but also SL and TL which affected the meaning of animal science terms. Different lexical choices of terms findings in the translation gave the effect of ambiguity and misunderstanding to the scientists as target readers, however, the solution was given in order to have an equivalence of understanding. It can be concluded that problematic of languages in both languages should be considered for improvement in translation.